The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1523/eneuro.0136-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Type-Selective Effects of Intramembrane Cavitation as a Unifying Theoretical Framework for Ultrasonic Neuromodulation

Abstract: Diverse translational and research applications could benefit from the noninvasive ability to reversibly modulate (excite or suppress) CNS activity using ultrasound pulses, however, without clarifying the underlying mechanism, advanced design-based ultrasonic neuromodulation remains elusive. Recently, intramembrane cavitation within the bilayer membrane was proposed to underlie both the biomechanics and the biophysics of acoustic bio-effects, potentially explaining cortical stimulation results through a neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
211
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 197 publications
(230 citation statements)
references
References 50 publications
19
211
0
Order By: Relevance
“…For example, we note that membrane mechanoelectrical effects involving dimensional changes were suggested in other contexts involving changes in intramembranal forces, including action potential-related intramembrane thickness variations [51][52][53] and ultrasoundinduced formation of intramembrane cavities (or "bilayer sonophores" [54]). The neuronal intramembrane cavitation excitation theoretical framework putatively explains ultrasonic neuromodulation phenomena (suppression and excitation [55]) and predicts the results of a significant number of related experimental studies [56,57].…”
Section: Discussionmentioning
confidence: 80%
“…For example, we note that membrane mechanoelectrical effects involving dimensional changes were suggested in other contexts involving changes in intramembranal forces, including action potential-related intramembrane thickness variations [51][52][53] and ultrasoundinduced formation of intramembrane cavities (or "bilayer sonophores" [54]). The neuronal intramembrane cavitation excitation theoretical framework putatively explains ultrasonic neuromodulation phenomena (suppression and excitation [55]) and predicts the results of a significant number of related experimental studies [56,57].…”
Section: Discussionmentioning
confidence: 80%
“…47 The study suggested that FUS intensity dictates whether a net outcome is an excitation or an inhibition as much as does a specific FUS pulsing protocol. In particular, short, repetitive pulses of the FUS—which correspond to low values of the duty cycle—are more likely to produce an inhibition, whereas longer repetitive pulses—higher duty cycle values—are more likely to lead to an excitation.…”
Section: Effective Stimulation Protocolsmentioning
confidence: 98%
“…39 FUS can excite or inhibit cellular activity, depending on specific stimulation parameters. 47 FUS can cause a transient increase in firing rates in motor cortex and in the retina with short latency, 39,55 and thus has a direct capability to influence cellular discharge. It has been hypothesized that these effects are mediated by ion channels that can detect changes in membrane stretch following a propagating pressure wave.…”
Section: Transcranial Focused Ultrasoundmentioning
confidence: 99%
See 2 more Smart Citations